Comparison Analysis of Hybrid Learning and Full Online toward Students' Critical Thinking Skills - Taofan Ali Achmadi; Devi Anggriyani; Sapitri Januariyansah; Ayub Budhi Anggoro (Universitas Negeri Semarang, 2024)
This study aims to compare the effectiveness of hybrid learning and fully online learning in enhancing students' critical thinking skills. The research employs a quasi-experimental design with a nonrandomized control group and pretest-posttest approach, involving 90 sixth-semester students from the Family Welfare Education Study Program at Semarang State University. Participants were divided into two groups: hybrid learning and fully online learning, with 45 students each. The instruments used included validated and reliable critical thinking tests and open-ended questionnaires to gather data on learning experiences. Data analysis utilized descriptive and inferential statistics, including paired t-tests and independent t-tests, with preliminary normality and homogeneity assessments. The results indicate significant improvement in critical thinking skills with both learning methods, but hybrid learning showed a more substantial increase in scores (p < 0.000) compared to fully online learning (p < 0.006). Thus, hybrid learning is more effective in fostering critical thinking skills, underscoring the benefits of combining face-to-face and online learning for optimal student development.